A Cross-sectional study Comparing Performance of IOTA Simple Rules, Simple Rules Risk Assessment and O-RADS in differentiating between Benign and Malignant Adnexal Lesions in a Tertiary Care Centre, Chengalpattu District - S.V, Arun; . B, Harshavardhan; Paul Raj, Jenikar; R, Remya. (Journal of Neonatal Surgery, 2025)
Background: Grading systems like IOTA Simple Rules and O-RADS are commonly used to assess ovarian lesions, but their comparative effectiveness in clinical practice remains underexplored. Objective: To evaluate and compare the performance of IOTA simple rules, simple rules risk assessment and O-RADS in differentiating between benign and malignant adnexal lesions. Methods: This was a single center, hospital based cross-sectional study conducted in the Department of Radiodiagnosis, Shri Sathya Sai Medical College and Research Institute, Kancheepuram, Tamil Nadu between July 2023 and December 2024. Results: The study included 128 participants, of whom 96 (75%) had benign adnexal masses and 32 (25%) had malignant lesions. The mean age of participants was 48.6 years, with no significant age difference between benign and malignant groups (p = 0.920). The majority of participants were under 50 years of age. In terms of lesion size, the mean maximum dimension was significantly larger for malignant lesions (100.5 mm) compared to benign lesions (83.0 mm, p < 0.001). Solid tissue was more common in malignant lesions (87.5%) compared to benign lesions (34.4%, p < 0.001). When using the IOTA Simple Rules, 74.2% of lesions were classified as benign, 16.4% as malignant, and 9.4% as inconclusive. The IOTA Simple Rules Risk Assessment categorized 45.3% of lesions with a malignancy risk of less than 1%, while 21.1% were classified with a risk of 50% or higher. The O-RADS classification showed that 68.0% of lesions were O-RADS 2 (benign), and 16.4% were O-RADS 5 (high risk). The IOTA Simple Rules Risk Assessment demonstrated an AUC of 0.922 (sensitivity: 81.3%, specificity: 82.7%), while the O-RADS system showed an AUC of 0.854 (sensitivity: 90.6%, specificity: 83.7%). Both systems were statistically significant (p < 0.001) in predicting malignant adnexal masses. Conclusion: Both the IOTA Simple Rules and O-RADS systems are effective in differentiating benign and malignant adnexal masses, with high diagnostic accuracy. The findings support their utility in improving clinical decision-making and patient outcomes